DECONSTRUCTION OF TIME AND SPACE IN THE PROSE OF EMIGRATION OF THE 20TH CENTURY (IN THE CONTEXT OF AZERBAIJANI AND MACEDONIAN LITERATURE) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
The article examines the deconstruction of time and space in the emigration literary heritage of 20th-century Azerbaijani and Macedonian literature. In this context, the creative works of the Azerbaijani writer Banine and the Macedonian writer Stoyan Christowe are taken as the main focus of analysis. Both writers left their homelands at a young age and lived and created in exile – one in France and the other in the United States. Given the richness of their literary output, two representative novels from each author, particularly relevant to the resolution of the problem under study, have been selected for detailed analysis. Within the framework of the research, it is emphasized that in the selected works, influenced by the experience of exile, time transcends its traditional structural form and is reconstructed as an aesthetic and ideological dimension, effectively undergoing deconstruction. In the novels of both writers, time is not presented as an objective measure that progresses in chronological order; rather, it appears as a fragmented flow of subjective memory, trauma, and nostalgia. Space, on the other hand, loses its geographical concreteness and takes on a more psychological and symbolic character. The article is conducted in a comparative framework using philological methods of analysis. The research reveals that emigration literature is not merely of individual significance, but also serves broader functions, including the preservation of national and cultural identity, the transmission of historical memory, and the artistic reconstruction of spatial and temporal concepts.
Keywords: Azerbaijani literature; Macedonian literature; emigration prose; time; space; deconstruction.